A facile method to fabricate proton-conducting BaZr0·85Y0·15O3-δ electrolyte with a large grain size and high conductivity. Issue 18 (15th December 2019) - Ge, Lin; Jiao, Jiahui; zhu, Zongchao; Zhang, Qixi; Zheng, Yifeng; Chen, Han; Guo, Lucun
Abstract: Y-doped BaZrO3 has been widely investigated as an electrolyte material for intermediate-temperature solid oxide fuel cells, However, its poor sinterability and high grain boundary resistance are major barriers to its practical application. In the present research, large-grained and high-conductive BaZr0·85 Y0·15 O3- δ (BZY15) electrolytes are fabricated via a facile method using Ba(NO3 )2 and (ZrO2 )0·92 (Y2 O3 )0.08 as the starting materials. For comparison, BaCO3 and Ba(CH3 COO)2 are also used as Ba sources to prepare BZY15. Micro-analysis indicates that BZY15 powders with large particle sizes and a homogenous morphology could be obtained at very low temperature due to the liquid phase environment provided by Ba(NO3 )2 . The Ba(NO3 )2 -derived pellet presents a homogeneous composition, in contrast to the Y segregation observed in the BaCO3 - and Ba(CH3 COO)2 -derived pellets after sintering. Moreover, the widely used sintering aid, NiO, could further improve the sinterability and electrical properties of BZY15. The resulting BZY15 electrolyte shows a high conductivity of 3.9 × 10 −3  S cm −1  at 600 °C.